IDENTIFIKASI SEBARAN ANOMALI MAGNETIK DI PERAIRAN KABUPATEN SAMBAS KALIMANTAN BARAT DENGAN MENGGUNAKAN METODE GEOMAGNET - Aripin, Aripin; Ivansyah, Okto; Sampurno, Joko (Universitas Negeri Semarang, 2017)
The distribution of magnetic anomalies in Sambas Sea has been investigated using the Magnetic method. The raw data, which acquired, have been corrected using IGRF data and tie-line leveling to obtain the local magnetic field distribution. Then, from the corrected data obtained four anomalous zones. Next, a slice that lying on the anomalous zones (line AB, CD, EF, and GH) was made to obtain the subsurface structures which obtain using inversion method. The results show that the presence of magnetic anomalies at the lines AB, EF and GH (with susceptibility values between 1.2 to 19.2) due to the magnetite rock at the subsurface. Moreover, The presence of magnetic anomalies at the line CD (with susceptibility values of 0.3 to 3.5) is caused by ilmenite rock. The correlation coefficients between the observation data and calculated data for all lines are between 0.98 to 0.99.